2019
DOI: 10.1159/000503415
|View full text |Cite
|
Sign up to set email alerts
|

Macular Hole Surgery in the Case of Wet Age-Related Macular Degeneration Treated with Intravitreal Aflibercept

Abstract: A 72-year-old male treated with aflibercept (Eylea) due to choroidal neovascularization (CNV) in his left eye developed a full-thickness macular hole (MH) after the second injection. The occurrence of MH in his left eye resulted in further visual acuity deterioration. As a consequence of having developed the MH, the patient was operated on. Phacoemulsification and vitrectomy with internal limiting membrane peeling and 20% SF6 tamponade were performed. MH closure was achieved and best corrected visual acuity im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Until now, only a few cases describe FTMH formation as a cause of visual decrease after intravitreal injection of anti-VEGF agents for neovascular AMD, like ranibizumab (sixteen cases) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ] and bevacizumab (two cases) [ 14 , 15 ]. Eight cases were reported after aflibercept intravitreal injection [ 10 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, only a few cases describe FTMH formation as a cause of visual decrease after intravitreal injection of anti-VEGF agents for neovascular AMD, like ranibizumab (sixteen cases) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ] and bevacizumab (two cases) [ 14 , 15 ]. Eight cases were reported after aflibercept intravitreal injection [ 10 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although anti-VEGF therapy is an effective treatment for MNV and macular edema in neovascular AMD, myopic choroidal neovascularization, polypoidal choroidal vasculopathy, retinal vein occlusion, etc., a limited number of ocular adverse events including endophthalmitis, increased intraocular pressure, retinal tear or detachment, retinal pigment epithelium tear, retinal ischemia, traumatic cataract, uveitis, and vitreous hemorrhage have been reported [ 2 ]. Full-thickness macular hole (FTMH) formation following intravitreal injections is rare and has only been reported in a few case reports and case series, mostly in association with neovascular AMD and in the presence of vitreomacular traction (VMT) disease [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Herein, we present a patient who developed a FTMH following intravitreal aflibercept injections for the treatment of MNV associated with AMD.…”
Section: Introductionmentioning
confidence: 99%
“…Tractional FTMHs may form by tangential or anteroposterior vitreous traction, ERM, PED, or changes in the CNV membrane. 9,10,25 Although degenerative FTMHs may be caused by atrophic process of the retina secondary to collapsed PED or macular scarring, 8 Cohen et al described retinal pseudocysts in a subset of eyes presenting with geographic atrophy. It was corresponded to optically empty spaces, frequently located in the inner nuclear layer, and they suggested that pseudocysts might correspond to Müller cell degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis might be tractional from anteroposterior or tangential vitreomacular traction with or without CNV contraction or degenerative which results from a atrophic processes in the underlying choroid and malfunctioning RPE. [8][9][10] Anti-vascular endothelial growth factor intravitreal injections can also induce vitreoretinal traction leading to the development of a FTMH or anti-vascular endothelial growth factor itself can modulate the activity of CNV and induce contraction of the membrane which may result in FTMHs. [11][12][13] For FTMHs in the presence of AMD, success rates for anatomical closure after pars plana vitrectomy range between 75% and 89% 11,14,15 and considered significantly lower in comparison with idiopathic FTMHs with anatomical success rates of above 90%.…”
mentioning
confidence: 99%
“…Epidemiological studies have shown that postmenopausal women have greater incidence of FTMHs, presumably due to decreases in estrogen leading to vitreous contraction [4]. To our knowledge, only 9 cases of FTMH formation after intravitreal aflibercept injection have been reported [5][6][7][8][9][10][11]. Multiple studies have delineated the capability of optical coherence tomography (OCT) in accurately diagnosing retinal pathologies such as PVD [12], subretinal hemorrhage [13], outer retinal hyperreflective deposits [14], and optic disk pit maculopathy [15].…”
Section: Introductionmentioning
confidence: 99%